Community health and public health nursing : a systematic literature review - Cunha, Carmen Maria Santos Lopes Monteiro; Costa, Andreia Cátia Jorge Silva; Henriques, Maria Adriana Pereira (Revista Gestão & Saúde, 2020)
Community health and public health nursing is a relevant issue in the context of the Portuguese National Health System reforms. International organizations, such as the World Health Organization, have emphasized the importance of nurses in community and public health care, and international studies report ongoing changes in this area in many countries. Through a Systematic Literature Review, conducted in early 2019, following an Equator Network protocol, Systematic Reviews, CRD’s guidance for undertaking reviews in health care, prepared by York University, we addressed the research issue: what has been published about community health and public health nurse competencies and interventions. The inclusion of articles followed PRISMA 2009 and 36 of the total number of publications were selected. The contributions refer to the expansion of nurses’ competences, events such as health fairs, nutrition, and caries assessments, performance in contexts of natural disasters, development of management skills, understanding and influencing the making of public health policies. With the ongoing public health reform taking place in Portugal, it is also a good opportunity for nursing to investigate, produce, innovate, and recreate itself.